Innovative Industry Engaged Project-Based Learning for Civil Engineering Structural Design - Lloyd, Natalie; Bland, K. (2014)
Review of the Bachelor of Engineering program is being undertaken in order to ensure compliance with AQF Level 8 requirements and continuing and improved Engineers Australia accreditation. Modifications to the final year Civil Engineering honours research project units are being implemented, making the curriculum more research-informed. Given that there will now be greater emphasis on research units within the program structure, enhancement of the assessment practices to ensure equitable and consistent assessment for all undergraduate research projects is being instigated. The proposed enhancements to the teaching delivery and assessment practices in final year honours research units in Civil Engineering aim to improve graduate research capabilities and improve graduate written and verbal communication in professional and lay contexts. Innovation in assessment will be undertaken to ensure industry engagement and participation in the process and lay the foundation for future WIL opportunities for the research units.